Determinants of urinary albumin excretion within the normal range in patients with type 2 diabetes: the Randomised Olmesartan and Diabetes Microalbuminuria Prevention (ROADMAP) study - Ritz, Eberhard; Viberti, G. C.; Ruilope, L. M.; Rabelink, A. J.; Izzo, J. L.; Katayama, S.; Ito, S.; Mimran, A.; Menne, J.; Rump, L. C.; Januszewicz, A.; Haller, H. (Diabetologia, 2010)
In contrast to microalbuminuric type 2 diabetic patients, the factors correlated with urinary albumin excretion are less well known in normoalbuminuric patients. This may be important because even within the normoalbuminuric range, higher rates of albuminuria are known to be associated with higher renal and cardiovascular risk.